TREN YANG MUNCUL DALAM ANALISIS BIG DATA: PELUANG UNTUK INTELIJEN BISNIS - Rini Wijayaningsih; Adinda Aisyah, Alghifari Arya Renato, Devina Amelia Putri, Devi Purnilasari, Dita Listiyana, Jeklyn (ADISAM PUBLISHER, 2024)
Big Data analytics has become a major focus in the business world to uncover valuable patterns, trends, and insights from large and complex amounts of data.This article aims to explore emerging trends in Big Data analytics as well as the opportunities it presents for business intelligence. Qualitative methods are used to analyze and analyze literature studies through library research. The results show that there are several emerging trends in Big Data analytics, including the use of advanced data analysis techniques such as machine learning and data mining, the integration of diverse data sources, and an increased focus on realtime analytics. In addition, this article also identifies various opportunities offered by Big Data analytics in the context of business intelligence, such as the ability to forecast market trends, detect anomalies, and improve data-driven decision making. By leveraging these trends, companies can optimize their business strategies, improve operational efficiency, and create added value for their customers. However, challenges such as data privacy, information security, and technological infrastructure limitations also need to be overcome in order for the implementation of Big Data analysis to be successful.